Pengaruh Komitmen Organisasi Terhadap Kinerja Pegawai Melalui Disiplin Kerja Sebagai Variabel Intervening Pada Dinas Kelautan dan Perikanan Provinsi Jambi - Jessica Melyana Br Manalu; Zulfina Adriani; Sumarni Sumarni (Pusat Riset dan Inovasi Nasional, 2024)
Employee performance in organizations is an essential aspect of managing human resources. Therefore, special attention is needed so that they are able to contribute to organizational success. This study aims to describe and determine the description and effect of organizational commitment on employee performance through work discipline as an intervening variable at the Jambi Province Maritime and Fisheries Service. The analysis method used is quantitative analysis using a Likert scale. The research population was all employees of the Jambi Provincial Maritime and Fisheries Service totaling 147 people. The number of samples in this study amounted to 60 people. Data collection techniques through questionnaires submitted to respondents. The data is processed using SmartPLS software version 4.0. The results showed that organizational commitment has a positive and significant effect on employee performance, organizational commitment has a positive and significant effect on work discipline, work discipline has a positive and significant effect on employee performance and work discipline mediates the effect of organizational commitment on employee performance.